Situation Report: Romania, 5 May 1965 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Chou En-lai [Enlai Zhou] Receives Romanian Delegations Cornel Manescu's Visit to UAR Draghici's May 1 Speech - Protests over Vietnam Krupp Manager Back to Essen from Bucharest Planning Achievements in the First Three Months of 1965 Austrian Industrial Exhibition Opens in Bucharest New Chairman of the Romanian Chamber of Trade Pope's Easter Greetings to Romanian Bishops Miscellaneous